Celecoxib Exerts Neuroprotective Effects in β-Amyloid-Treated SH-SY5Y Cells Through the Regulation of Heme Oxygenase-1: Novel Insights for an Old Drug - Mhillaj, Emanuela; Papi, Massimiliano; Paciello, Fabiola; Silvestrini, Andrea; Rolesi, Rolando; Palmieri, Valentina; Perini, Giordano; Fetoni, Anna Rita; Trabace, Luigia; Mancuso, Cesare (Frontiers in Cell and Developmental Biology, 2020)
The formation and aggregation of amyloid-β-peptide (Aβ) into soluble and insoluble species represent the pathological hallmarks of Alzheimer’s disease (AD). Over the last few years, however, soluble Aβ (sAβ) prevailed over fibrillar Aβ (fAβ) as determinant of neurotoxicity. One of the main therapeutic strategies for challenging neurodegeneration is to fight against neuroinflammation and prevent free radical-induced damage: in this light, the heme oxygenase/biliverdin reductase (HO/BVR) system is considered a promising drug target. The aim of this work was to investigate whether or not celecoxib (CXB), a selective inhibitor of the pro-inflammatory cyclooxygenase-2, modulates the HO/BVR system and prevents lipoperoxidation in SH-SY5Y neuroblastoma cells. Both sAβ (6.25-50 nM) and fAβ (1.25-50 nM) dose-dependently over-expressed inducible HO (HO-1) after 24 hours of incubation, reaching statistical significance at 25 nM and 6.25 nM, respectively. Interestingly, CXB (1-10 µM, for 1 hour) further enhanced Aβ-induced HO-1 expression through the nuclear translocation of the transcriptional factor Nrf2. Furthermore, 10 µM CXB counteracted the Aβ-induced ROS production with a mechanism fully dependent on HO-1 upregulation; nevertheless, 10 µM CXB significantly counteracted only 25 nM sAβ-induced lipid peroxidation damage in SH-SY5Y neurons by modulating HO-1. Both carbon monoxide (CORM-2, 50 nM) and bilirubin (50 nM) significantly prevented ROS production in Aβ-treated neurons and favored both the slowdown of the growth rate of Aβ oligomers and the decrease in oligomer/fibril final size. In conclusion, these results suggest a novel mechanism through which CXB is neuroprotective in subjects with early AD or mild cognitive impairment.